2019
DOI: 10.1097/brs.0000000000003082
|View full text |Cite
|
Sign up to set email alerts
|

Age-related Changes in Cervical Sagittal Alignment

Abstract: Study Design. Retrospective cohort study. Objective. To identify age-related changes in cervical sagittal parameters using standard radiographs. Summary of Background Data. Cervical sagittal balance is important for the maintenance of neutral head posture and horizontal gaze. Degenerative changes in the cervical spine that occur with aging may alter cervical sagittal balance, which can lead to chronic neck p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 32 publications
4
13
1
Order By: Relevance
“…We found that cervical lordosis increased with age (Figure 2), as described in several previous radiographic studies (Guo et al, 2011; Inoue et al, 2020; Tang et al, 2019; Virk et al, 2020; Yeh et al, 2018; Yukawa et al, 2012, 2018; Zhou et al, 2020). However, the effect of age on cervical lordosis remains controversial.…”
Section: Discussionsupporting
confidence: 86%
“…We found that cervical lordosis increased with age (Figure 2), as described in several previous radiographic studies (Guo et al, 2011; Inoue et al, 2020; Tang et al, 2019; Virk et al, 2020; Yeh et al, 2018; Yukawa et al, 2012, 2018; Zhou et al, 2020). However, the effect of age on cervical lordosis remains controversial.…”
Section: Discussionsupporting
confidence: 86%
“…In addition, we found significant differences in curvature between younger and older healthy participants. More specifically, consistent with the existing spinal cord literature, cervical vertebrae two to four appear to increase in curvature with age [22][23][24][35][36][37][38].…”
Section: Discussionsupporting
confidence: 81%
“…Upon analyzing 21 studies, the authors found curvature was not significantly different between symptomatic and asymptomatic individuals, and age was not significantly associated with amount of lordotic cervical curvature. Interestingly, other studies have found that the angle of cervical lordosis tends to increase with age [34][35][36][37]. The parameter of interest for all of these studies was cervical lordosis -where the spine is curving posteriorly (see the image to the left of Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Abelin-Genovois et al 78 ports, aged population showed increases cervical SVA, CL, and T1S which is mainly contributed from increased TK. 4,[87][88][89][90][91][92][93][94][95] Chen et al 96 (2017) and Liu et al 97 (2019) presented increasing TIA and NT with aging process as well as CL and T1S.…”
Section: Normal Alignment and Compensation; Intra-and Extracervical Smentioning
confidence: 99%